A review on antidepressant effect of medicinal plants (Bangladesh Journal of Pharmacology, 2017)
Depression is a life-threatening, debilitating, and common disease affecting different segments of community. Chemical and synthetic drugs available to treat this disease cause many adverse effects and may lead to complete recovery in only 50% of patients. At the same time, medicinal plants have been reported to exert optimal pharmacological effects in treating depression in different models. In this review, the relevant articles indexed in the reliable databases PubMed, PubMed central, Scopus and Web of Science were review-ed. The review indicated that most medicinal plants exerted antidepressant effects through synaptic regulation of serotonin, noradrenaline, and dopamine, regulating activity of hypothalamic-pituitary-adrenal axis, reinfor-cing anti-oxidant defense system, and decreasing inflammatory mediators. The medicinal plants and their active compounds can relieve depression through different pathways and hence are considered a new source to produce antidepressants.